2023
DOI: 10.1108/jcefts-04-2022-0025
|View full text |Cite
|
Sign up to set email alerts
|

Food security and political instability-foreign divestment analysis

Abstract: Purpose Prior studies have found evidence for the role of political instability on foreign divestment (FD) where a high level of instability encourages FD decisions. Therefore, this paper aims to examine how the food security level explains the linkage between political instability and FD. Design/methodology/approach The current study adopts the system generalised method of moment (GMM) to achieve accurate and reliable empirical evidence for 60 developing countries in the period 2011 to 2020. Findings The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 30 publications
(46 reference statements)
0
1
0
Order By: Relevance
“…For instance, Vega (2015) found that the absence of social security benefits, such as healthcare and pension schemes, led migrants to return to their home country once they retired. Similarly, a study conducted by Subramaniam et al (2023) observed that migrants from countries with weak social security systems tended to remit more funds to ensure the well-being of their families.…”
Section: Literature Reviewmentioning
confidence: 98%
“…For instance, Vega (2015) found that the absence of social security benefits, such as healthcare and pension schemes, led migrants to return to their home country once they retired. Similarly, a study conducted by Subramaniam et al (2023) observed that migrants from countries with weak social security systems tended to remit more funds to ensure the well-being of their families.…”
Section: Literature Reviewmentioning
confidence: 98%